The impact of regional autonomy and monetary crisis on economic growth in Yogyakarta - Sarastri Mumpuni Ruchba; Ferdy Suhada (Economic Journal of Emerging Markets, 2015)
This study analyzes the impact of some factors, especially the implementation of autonomy and monetary crisis on economic growth in Yogyakarta Special Province. The independent variables entered into the model are investment, labor force and government spending, as well as two dummy variables, namely the financial crisis and the 1990-2013 regional autonomy implementations. This study uses multiple linear regression analysis with Ordinary Least Square (OLS). This study finds that investment and regional autonomy do not affect the economic growth in Yogyakarta, while labor force and monetary crisis negatively affect economic growth. The study also finds that government spending has a positive influence on economic growth.